Analisis Patologi Birokrasi dalam Kualitas Pelayanan Publik di Kantor Kecamatan Pinang Kota Tangerang - Pradana, Indah Agustin; Anisa, Rizky; Zahra, Hanifa; Kamila, Diah Fitri; Prasetyo, Eko (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
Bureaucratic pathology refers to conditions in which the bureaucracy or public administration system, which is supposed to help and serve the community, actually becomes an obstacle and makes it difficult to provide good service. Bureaucratic pathology is usually characterized by ineffective, inefficient and non-transparent bureaucratic behavior. This study used a descriptive qualitative research method, with key informants namely the Head of the Public Services Section of the Pinang District Office and the people receiving services in Pinang District, Tangerang City. Data collection was carried out by interviews, field notes, documentation studies, and other official documents obtained from informants. The purpose of this study is to reveal the facts and situations that occur regarding the existence of bureaucratic pathology in public services in Pinang District, Tangerang City. The results showed that there was no bureaucratic pathology in public services carried out by the Pinang District Office, Tangerang City, but there were several obstacles that occurred, namely the problem of blanks and the network system (internet) which sometimes had problems. The existence of these obstacles if not overcome will reduce the effectiveness and efficiency of services.